HUBUNGAN TINGKAT STRES DENGAN KEJADIAN SINDROMA DISPESPSIA PADA ANAK USIA 10-14 TAHUN DI WILAYAH KERJA PUSKESMAS BLUTO - Zakiyah Yasin; Nailiy Huzaimah; Hariyanto Hariyanto (Wiraraja Medika : Jurnal Kesehatan, 2018)
Syndrome dyspepsia often occurred and still be health problems in the society. The prevalence of cases of occurrence of symptoms syndrome dyspepsia in Western countries is around 23%-41% and in Indonesia the case of syndrome dyspepsia that came for medical to health services about 30%-60%. The cause of the symptoms of the syndrome dyspepsia is afactor of stress. This research purposed to know the relation of stress level with incident syndrome dyspepsia. The research was carried out on children ages 10-14 years in the working area Bluto Puskesmas. This research use analytic correlative study design with crosssectional approach (α = 0,05). The respondents in this study amounted to 47 people who are taked by using simple random sampling. The instruments used are questionnaire DASS 42 to measure the stress levels and Form Check List to measure incidence syndrome dyspepsia. Data analysis using the Coefficient Contingency Test to find out the relation between the two variables. The results showed no relationship stress levels with occurrence syndrome dyspepsiain children age 10-14 years who are in the working area Bluto Puskesmas (p = 0.327.r = 0.213). Many levels of stress occurs is mild stress level while the symptoms of the syndrome dyspepsia are most dominant is heartburn when hungry. The factors that caused the syndrom dyspepsia in children not just because factor of stress, but several the other factors also affect happen syndrome dyspepsia like an increase in the secretion of gastric acid, Helicobacter pylori infection, Dismotitilitas gastrointestinal stimulation threshold of perception, autonomic Dysfunction, the activity of the gastric mioelektrik, the role of Diet, hormonal and environmental factors, psychological, and genetic factors. Need to be researched again the other factors that might relate to or be the cause of the syndrome dyspepsia in children ages 10-14 years in the working area Bluto Puskesmas.